2013
DOI: 10.1073/pnas.1219125110
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional insights into caseinolytic proteases reveal an unprecedented regulation principle of their catalytic triad

Abstract: Caseinolytic proteases (ClpPs) are large oligomeric protein complexes that contribute to cell homeostasis as well as virulence regulation in bacteria. Although most organisms possess a single ClpP protein, some organisms encode two or more ClpP isoforms. Here, we elucidated the crystal structures of ClpP1 and ClpP2 from pathogenic Listeria monocytogenes and observe an unprecedented regulation principle by the catalytic triad. Whereas L. monocytogenes (Lm)ClpP2 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(102 citation statements)
references
References 40 publications
(64 reference statements)
7
84
0
9
Order By: Relevance
“…Thus, ClpP2 lacks activity against these types of tripeptides, although Z-nLPnLD-amc was hydrolyzed by ClpP1(S-A)P2 slightly faster than other substrates. Interestingly, in another bacterium containing ClpP1 and ClpP2 subunits, Listeria monocytogenes, the relative roles of ClpP1 and ClpP2 were quite different, with ClpP2 complexes proteolytically active by themselves, whereas ClpP1 subunits were only activated in the mixed ClpP1P2 complex (35). Despite their very different activities in tripeptide degradation, surprisingly, we found that both ClpP1 and ClpP2 subunits made major contributions to protein degradation.…”
Section: Distinct Specificity Of Peptide Bond Hydrolysis By Clpp1p2-mentioning
confidence: 67%
“…Thus, ClpP2 lacks activity against these types of tripeptides, although Z-nLPnLD-amc was hydrolyzed by ClpP1(S-A)P2 slightly faster than other substrates. Interestingly, in another bacterium containing ClpP1 and ClpP2 subunits, Listeria monocytogenes, the relative roles of ClpP1 and ClpP2 were quite different, with ClpP2 complexes proteolytically active by themselves, whereas ClpP1 subunits were only activated in the mixed ClpP1P2 complex (35). Despite their very different activities in tripeptide degradation, surprisingly, we found that both ClpP1 and ClpP2 subunits made major contributions to protein degradation.…”
Section: Distinct Specificity Of Peptide Bond Hydrolysis By Clpp1p2-mentioning
confidence: 67%
“…However, the strong selection acting on the plastid CLP complex in Silene suggests that both plastid-and nuclearencoded CLPP subunits may retain an important functional role despite changes in the catalytic triad (Table S8). Although the Ser-His-Asp catalytic site is a widely conserved feature across the diversity of life, some of the same substitutions in this triad have been observed in other atypical serine proteases and functionally related enzymes (Schrag et al 1991;Ekici et al 2008;Zeiler et al 2013). Notably, substitutions in the catalytic triad were only observed in one nuclear-encoded CLPP gene in each of the fast species.…”
Section: Loss Of Plastid Heteromeric Accasementioning
confidence: 83%
“…Importantly, this histidine has previously been identified as part of a hydrogen bonding network which plays a crucial role for the de-oligomerization process. 26 Thus, the relative orientation of the inhibitor scaffold of ML89 compared to ML90 may trigger a steric rearrangement which causes the observed de-oligomerization. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 …”
Section: Molecular Docking Reveals the Binding Mode Of Phenyl Estersmentioning
confidence: 99%
“…26 Moreover, in the compressed state all crucial interactions between the rings are abrogated leading to the formation of inactive heptamers. From a pharmacological perspective, inhibitor-induced heptamerization is advantageous as the corresponding enzyme, although not quantitatively acylated, is misaligned and inactive in all catalytic centers, effectively maximizing the sustainability of deactivation.…”
Section: Introductionmentioning
confidence: 99%